Affective Temperaments and Age of Onset in Bipolar Type II Patients - Lolich, María; Romero, Ester; Vázquez, Gustavo (Revista de Psicología, 2016)
Nowadays it is imperative to have predictors that allow an early and accurate detection of bipolar disorder, in general and bipolar type II disorder, in particular. Affective temperaments refer to different types of emotional reactivity, which are temporarily stable throughout the life cycle and demonstrate a relevant biological basis. Given the lack of previous research, possible relations between the onset age of 32 euthymic patients diagnosed with bipolar II disorder, and the cyclothymic, depressive, irritable, anxious and hyperthymic affective temperaments features were explored. The participants had an average age of 51.5 (interquartile range: 8) and 65.6% of the sample were men. A high and significant inverse correlation was found between the onset age of bipolar disorder and depressive temperament. Between cyclothymic, irritable and anxious temperaments, correlations were statistically significant, although moderate and inverse. Hyperthymic temperament did not significantly correlate with the onset age. When performing multivariate linear regression analyses, no satisfactory models were found. The systematic evaluation of affective temperaments, in those individuals who are prone to develop an affective disorder, should be included in the set of common evaluation techniques.